STUDY OF PREFERENCES FOR STUDENT COMMUNAL SPACE IN THE UPN VETERAN JAWA TIMUR - Dominikus Aditya Fitriyanto; Yerry Kahaditu Firmansyah; Azkia Avenzoar (Border: Jurnal Arsitektur, 2024)
The communal space for students in the university is important to support academic activities, considering that student activities on campus are not only in classrooms, studios, laboratories, and libraries. However, these shared areas are often poorly designed, leading to disruptions and discomfort for users. This research aims to gather preferences for student communal spaces at UPN "Veteran" Jawa Timur. The research objectives include identifying perceptions of the availability of student communal spaces and the activities carried out in these spaces. Furthermore, it aims to identify expectations for the atmosphere and facilities in these communal spaces. The results of the analysis of these expectations for the atmosphere and facilities are then linked to the types of activities. This research is conducted using a qualitative method. Data is collected through online questionnaires distributed to UPN "Veteran" Jawa Timur students and then analyzed using content analysis with stages including open coding, axial coding, and selective coding. The results show that psychological atmosphere factors, as well as thermal, auditory, and visual comfort, are dominant in the desired atmosphere by respondents. Additionally, the expected facilities are electronic and electrical.